2008
DOI: 10.1002/asia.200800114
|View full text |Cite
|
Sign up to set email alerts
|

A Femtosecond Study of the Interaction of Human Serum Albumin with a Surfactant (SDS)

Abstract: The interaction of a protein, human serum albumin (HSA) with a surfactant (sodium dodecyl sulfate, SDS) was studied by femtosecond up-conversion. HSA was labeled covalently with a probe (CPM, 7-dimethylamino-3-(4-maleimidophenyl)-4-methylcoumarin). Binding of SDS to HSA is found to accelerate the solvation dynamics approximately 1.3-fold. The solvation dynamics in HSA displays two time components: 30 ps (20 %) and 800 ps (80 %). When approximately 10 SDS molecules bind to HSA the components are 15 ps (40 %) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…It is observed that the native HSA exhibits two ultraslow solvation time components of 30 ps and 800 ps. 26 On addition of 1.5 M RTIL or 6 M GdnHCl to the native protein, one ultrafast component of 1 ps along with the ultraslow components (30 ps, 800ps for 1.5 M RTIL and 100 ps for 6 M GdnHCl) are observed. The average solvation time in presence of 1.5 M RTIL ( τ ∼260 ps) and 6 M GdnHCl ( τ ∼60 ps) becomes ∼2.5 times and ∼11 times faster, respectively, compared to that in native HSA ( τ ∼650 ps).…”
Section: Solvation Dynamics Of Cpm Bound To Hsa: Effect Of Rtilmentioning
confidence: 94%
See 3 more Smart Citations
“…It is observed that the native HSA exhibits two ultraslow solvation time components of 30 ps and 800 ps. 26 On addition of 1.5 M RTIL or 6 M GdnHCl to the native protein, one ultrafast component of 1 ps along with the ultraslow components (30 ps, 800ps for 1.5 M RTIL and 100 ps for 6 M GdnHCl) are observed. The average solvation time in presence of 1.5 M RTIL ( τ ∼260 ps) and 6 M GdnHCl ( τ ∼60 ps) becomes ∼2.5 times and ∼11 times faster, respectively, compared to that in native HSA ( τ ∼650 ps).…”
Section: Solvation Dynamics Of Cpm Bound To Hsa: Effect Of Rtilmentioning
confidence: 94%
“…They were detected from a picosecond setup described in our earlier works. 26,47 The typical FWHM of the system response using a liquid scatterer is about 90 ps. The picosecond fluorescence decays were deconvoluted using IBH DAS6 software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Amongst the foremost threat to cardiovascular and renal disorders, hypertension is a widespread and frequently progressive ailment. [12][13][14] BSA and Human Serum Albumin (HSA) are the most studied serum proteins in pharmaceutical industry due to their ability to bind various drug molecules and alter their pharmacokinetic/ pharmacodynamic properties. Among the many classes of antihypertensives, angiotensin converting enzyme (ACE) inhibitors are commonly used to treat cardiovascular diseases such as high blood pressure, heart failure, coronary/artery disease and kidney failure which inhibits the conversion of angiotensin I to angiotensin II.…”
Section: Introductionmentioning
confidence: 99%